Identifying the Determinants of Attitudes towards Immigrants - A Structural Cross-Country Analysis - Jan Brenner; Michael Fertig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
Utilizing subjective data to infer on fundamental issues of individual opinion is associated with severe conceptual and methodological problems.This paper addresses these problems and investigates the attitudes towards immigrants within a cross-country framework. To this end, we utilize data from the first wave of the European Social Survey (ESS) in a structural latent variable model. The determinants of attitudes towards immigrants are estimated by employing different identification restrictions on the model. Our results suggest that educational attainment as well as parental education are the main driving forces behind attitudes formation.Average attitudes across countries further seem to increase with per capita GDP. All our findings are stable across countries and identification strategies.
Keywords: F22; C31; J15; 330; Subjective Data; Identification; Minorities